Screening for seedling stage salinity tolerance and comparative transcriptome analysis in Rice (Oryza sativa L.) (Indian Journal of Experimental Biology (IJEB), 2022)
Soil salinity is one of the major abiotic stresses which affect crop productivity including rice, Oryza sativa L. Developing salt tolerant varieties gained considerable attention accordingly. Here, we studied salinity tolerance in rice crop. We screened ten rice genotypes for saline tolerance at different concentrations of 0 dSm-1, 2 dSm-1, 4 dSm-1, 6 dSm-1, 8 dSm-1,10 dSm-1, 12 dSm-1 and 14 dSm-1, respectively. Among the ten genotypes studied, CARIDhan-7 tolerated salt stress up to 6dSm-1 of irrigated water. Comparative transcriptome analysis was done with the genotypes by treating with saline water at 0dSm-1 and 6 dSm-1. A total of 1013 genes were differentially expressed under simulated stress conditions. Out of which, 551 genes were upregulated and 462 genes were downregulated. Based on the metabolic pathway analysis, the MAPK signaling pathway, along with the other 9 pathways were found to be enriched in the stressed sample. Nine ion transporter genes, 1potassium channel, 1 protein phosphatase gene, IAA homologs OsIAA9, two ROS scavenging-related genes, and 4 stress regulated genes identified were found to be significantly up-regulated along with some functional proteins previously reported under salt stress. An AP2-like ethylene-responsive transcription factor PLETHORA 2 was found to be downregulated. The results suggested that the CARIDhan-7 genotype undergoes various saline tolerant mechanisms and pathways in response to the stress imposed when compared to non-stressed seedlings.